Grit in L2 Educational Contexts: A Scoping Review - Arfiandhani, Puput; Takeuchi, Osamu (ELT-Lectura, 2025)
The recent years saw the surge of interest in psychological constructs essential to L2 teaching and learning. Among these constructs, grit received significant attention in L2 field. The present scoping review investigates the methodological trends, geographical distribution, and study foci of grit in L2 educational contexts from 2020 to 2025. In the present review, 293 articles were initially identified from Proquest, JSTOR, and DOAJ databases (N = 293). In the end, 89 articles were assessed for eligibility, and 50 articles were included in the final review (n = 50). The findings of the scoping review include (1) quantitative methodologies dominated the retrieved articles, (2) studies in Asian contexts were predominantly found, and (3) L2 learners rather than L2 teachers are the focus of most articles. The present study underscores the need (1) to include qualitative findings in various cultural contexts, and (2) to conduct more grit studies with L2 teacher foci to provide more diverse insights into grit in L2 educational contexts. Keywords: grit, L2 educational contexts, scoping review, language learning psychology